Vegetable biocholine supplementation in lambs during the feed transition period improves health and enhances weight gain - Leal K.W.* (2021)
© 2021 Elsevier B.V.Lambs born from dairy ewes are removed from their mothers within hours of ingesting colostrum; this influences their growth and development, especially when artificial milk has poor quality or insufficient volume. Alternatives have been proposed to assist lambs during this phase, including providing concentrate with additives such as choline, which is involved in various physiological processes. This study's objective was to determine the effects of vegetable biocholine (VB) supplementation on growth, biochemistry, and antioxidant responses in lambs from dairy ewes during the feed transition period. We used 40 Lacaune lambs in a randomized block design, distributed in four groups with five replications (two animals per replication). VB was added to the concentrate and was consumed between 30 days pre-weaning to 30 days post-weaning (total 60 days). The treatments were as follows: T0, without added VB, control group; T2, 2 g VB per animal/day; T4, 4 g VB per animal/day; and T6, 6 g VB per animal/day. The weight gain increased in T2, T4, and T6 lambs when compared to T0. Using orthogonal polynomials analysis suggested that the ideal supplementation dose is 2.81 g/day per animal when considering the maximum average daily gain (ADG), which corresponds to 0.189 g VB/kg of body weight (BW). After weaning, there were lower serum concentrations of creatine kinase enzyme in lambs supplemented with VB than in controls. No differences were observed concerning levels of total protein, albumin, or globulins. Alanine aminotransferase (ALT) activity of T2 and T4 lambs was greater only at weaning (30 days). Glucose was greater in T2 and T4 lambs only on day 15. In general, VB supplementation decreased serum levels of reactive oxygen species (ROS) from day 15 of supplementation; these animals had lower lipid peroxidation levels after weaning. The activities of glutathione S-transferase (GST) did not differ. These data suggest that supplementation with VB increases weight gain and improves health, primarily by reducing free radical levels during the dietary transition period.